Deciphering the Plasmodium falciparum malaria-specific CD4+ T-cell response: ex vivo detection of high frequencies of PD-1+TIGIT+ EXP1-specific CD4+ T cells using a novel HLA-DR11-restricted MHC class II tetramer. (8th December 2021) - Schulte, Sophia; Heide, Janna; Ackermann, Christin; Peine, Sven; Ramharter, Michael; Mackroth, Maria Sophia; Woost, Robin; Jacobs, Thomas; Schulze zur Wiesch, Julian
Abstract: Relatively little is known about the ex vivo frequency and phenotype of the Plasmodium falciparum -specific CD4+ T-cell response in humans. The exported protein 1 (EXP1) is expressed by plasmodia at both, the liver stage and blood stage, of infection making it a potential target for CD4+ and CD8+ effector T cells. Here, a fluorochrome-labelled HLA-DRB1∗11:01-restriced MHC class II tetramer derived from the P. falciparum EXP1 (aa62-74) was established for ex vivo tetramer analysis and magnetic bead enrichment in 10 patients with acute malaria. EXP1-specific CD4+ T cells were detectable in 9 out of 10 (90%) malaria patients expressing the HLA-DRB1∗11 molecule with an average ex vivo frequency of 0.11% (0–0.22%) of total CD4+ T cells. The phenotype of EXP1-specific CD4+ T cells was further assessed using co-staining with activation (CD38, HLA-DR, CD26), differentiation (CD45RO, CCR7, KLRG1, CD127), senescence (CD57), and co-inhibitory (PD-1, TIGIT, LAG-3, TIM-3) markers as well as the ectonucleotidases CD39 and CD73. EXP1-specific tetramer+ CD4+ T cells had a distinct phenotype compared to bulk CD4+ T cells and displayed a highly activated effector memory phenotype with elevated levels of co-inhibitory receptors and activation markers: EXP1-specific CD4+ T cells universally expressed the co-inhibitory receptors PD-1 and TIGIT as well as the activation marker CD38 and showed elevated frequencies of CD39. These results demonstrate that MHC class II tetramer enrichment is a sensitive approach to investigate ex vivo antigen-specific CD4+ T cells in malaria patients that will aid further analysis of the role of CD4+ T cells during malaria. Abstract : EXP1-specific CD4+ T cells were detectable in 9 out of 10 (90%) malaria patients expressing the HLA-DRB1∗11 molecule using a novel MHC class II with an average ex vivo frequency of 0.11% of total CD4+ T cells. EXP1-specific CD4+ T cells universally expressed the co-inhibitory receptors PD-1 and TIGIT as well as the activation marker CD38 and showed elevated frequencies of CD39. Graphical Abstract: